Estudo da reticulação e propriedades mecânicas da blenda CM/CR - Souza, Pedro Zangrossi de (Universidade Federal de São Carlos, 2024)
The mechanical properties of the elastomeric blend of chlorinated polyethylene (CM) and polychloroprene (CR) were studied in the proportions CM: CR 90:10, 70:30, 50:50, 30:70 and 10:90, respectively called A, B, C, D, and E. The formulation of the blends was developed to minimize any variables other than the polymer content, guaranteeing the feasibility of industrial application on a large scale and in the short term, and the properties required to meet automotive standards. The choice of peroxide type and content made it possible to match all the samples to the same specification and achieve the proposed objectives. The samples were prepared in two mixing stages, first in a closed mixer and then in an open mixer, to equalize the processing history. Using the same curing system ensured a difference of around 10% in t50 and t90 in all polymer proportions. Complete vulcanization was achieved in less than 2.5 minutes. Hardness, tensile strength, elongation, and tear strength increased as the CM content increased. The elastic modulus and cost increased in the opposite direction.
Study of the crosslinking and mechanical properties of CM/CR blends
Keywords: Policloripreno; Polietileno clorado; Blenda; Vulcanização por peróxido; Borracha; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS